Isolating and Identifying One Strain with Lead-Tolerant Fungus and Preliminary Study on Its Capability of Biosorption to Pb2+ - Wanna Li; Liujing Zhao; Cui Liu; Xingpeng Bai; Chenyuan Xu; Fengqiu An; Feilong Sun (Biology)
To obtain lead-resistant microorganisms as potential strains for bioremediation, in this study, a strain of fungus with high resistance to lead was isolated and domesticated from lead-contaminated soil, which was cultured and molecularly biologically identified as the genus Sarocladium Pb-9 (GenBank No. MK372219). The optimal incubation time of strain Pb-9 was 96 h, the optimal incubation temperature was 25 °C, and the optimal incubation pH was 7. The strain Pb-9 had a good adsorption effect on Pb2+ at a lead concentration of 2000 mg/L; scanning electron microscopy (SEM) observed that the spores of the Pb-9 strain appeared to be wrinkled and deformed under Pb2+ stress, and XRD analysis showed that the mycelium of Pb-9 adsorbed Pb2+; Fourier transform infrared spectroscopy (FTIR) analysis showed that the Pb-9 strain might produce substances such as esters and polysaccharides under the treatment of different Pb2+ concentrations. The above results showed that strain Pb-9 has good resistance and adsorption capacity to lead. Therefore, it has potential application value in the bioremediation of environmental heavy metal pollution, and this study provides a fundamental basis for the bioremediation of lead pollution in the environment.